Broad band “Western Mediterranean” and ocean bottom “Fomar” seismological networks - Martin-Davila, J. (2007)
To study the seismicity associated to the Ibero-Maghrebian region, the Real Instituto y Observatorio de la Armada in San Fernando (ROA) has installed, since 1898, different types of seismological stations. At present two networks are in operation: Long Period station and Short Period net (ROA) and Western Mediterranean Broad Band (WM) net (in collaboration among several institutions). The installation of a network of ocean-bottom seismographs (FOMAR) is underway. The Ibero- Maghrebian region corresponds to the western part of the Eurasia-Africa plate boundary and is of great seismological and tectonic interest. It extends from 12oW to 3oE, comprising Southern Iberia and northern Africa, including the Gulf of Cadiz and Alboran Sea (figure 1). Seismicity is characterized by the occurrence of moderate and large magnitude earthquakes at shallow depth, intermediate depth earthquakes (30<h<150 km) and some very deep events (650 km). The whole area constitutes a broad deformation zone, without a well defined plate boundary line, with a plate convergence in a NNW-SSE direction at a rate of 1 to 5 mm/year (Buforn et al., 1995).